Sulphide sinking in magma conduits: evidence from maficultramafic plugs on Rum and the wider North Atlantic Igneous Province - Hughes, Hannah S. R.; McDonald, Iain; Boyce, Adrian J.; Holwell, D. A.; Kerr, Andrew Craig (Journal of Petrology, 2016)
Ni–Cu–PGE (platinum group element) sulphide mineralization is commonly found in magmatic conduit systems. In many cases the trigger for formation of an immiscible sulphide liquid involves assimilation of S-bearing crustal rocks. Conceptually, the fluid dynamics of sulphide liquid droplets within such conduits is essentially a balance between gravitational sinking and upwards entrainment. Thus, crustal contamination signatures may be present in sulphides preserved both up- and down-flow from the point of interaction with the contaminant. We examine a suite of ultramafic volcanic plugs on the Isle of Rum, Scotland, to decipher controls on sulphide accumulation in near-surface magma conduits intruded into a variable sedimentary stratigraphy. The whole-rock compositions of the plugs broadly overlap with the compositions of ultramafic units within the Rum Layered Complex, although subtle differences between each plug highlight their individuality. Interstitial base metal sulphide minerals occur in all ultramafic plugs on Rum. Sulphide minerals have magmatic δ34S (ranging from –1·3 to +2·1‰) and S/Se ratios (mean = 2299), and demonstrate that the conduit magmas were already S-saturated. However, two plugs in NW Rum contain substantially coarser (sometimes net-textured) sulphides with unusually light δ34S (–14·7 to +0·3‰) and elevated S/Se ratios (mean = 4457), not represented by the immediate host-rocks. Based on the Hebrides Basin sedimentary stratigraphy, it is likely that the volcanic con duits would have intruded through a package of Jurassic mudrocks with characteristically light δ34S (–33·8 to –14·7‰). We propose that a secondary crustal S contamination event took place at a level above that currently exposed, and that these sulphides sank back to their present position. Modelling suggests that upon the cessation of active magma transport, sulphide liquids could have sunk back through the conduit over a distance of several hundreds of metres, over a period of a few days. This sulphide ‘withdrawal’ process may be ...